Swelling kinetics of unsaturated polyester and their montmorillonite filled nanocomposite synthesized from glycolyzed PET - Katoch, Sunain; Sharma, Vinay; Kundu, Patit Paban (Diffusion Fundamentals, 2011)
The solvent resistance properties of the unsaturated polyster and their montmorillonite filled nanocomposites are studied in acetic through equilibrium swelling method at different temperatures. The kinetics of sorption is studied by using the equation of transport phenomena. The values of ‘n’ in solvent transport equation are found to be below ‘0.5’, showing the non-Fickian or pseudo-Fickian transport in the polymer. The dependence of diffusion coefficient on composition and temperature has been studied for all polymeric samples. The diffusion coefficient of unsaturated polyester samples decreases with an increase in unsaturated acid content. The nanocomposite samples show low diffusion coefficient than corresponding pristine polymers. The diffusion coefficient, sorption coefficient and permeation coefficient increase with an increase in temperature for all samples. The crosslink density for neat polymer with varied unsaturated acid content ranges from 2.98 to 3.52 ×105mol/cm3. For the nanocomposite samples it ranges from 3.70 to 5.72 × 105 mol/cm3.